PROINFLAMMATORY ROLE OF ANGIOTENSIN II IN THE AORTA OF NORMOTENSIVE MICE. (June 2018) - Lima, R.S.; Silva, J.C.S.; Lima, C.T.; Souza, L.E.; Baladi, M.G.; Irigoyen, M.C.; Lacchini, S.
Abstract : Objective: Angiotensin II exerts important physiological functions on cardiovascular system homeostasis and may mediate actions leading to inflammatory responses. This study aimed to verify the ability of angiotensin II to induce an inflammatory response in the aorta and if there is a relation with variations of arterial pressure, even if discrete. Design and method: For this, C57Bl/ 6 mice treated with saline solution (0.9%, control group) or Angiotensin II (30ng, Ang II group) were used. The animals were cannulated in the carotid artery and jugular vein, and 48 hours later blood pressure and heart rate levels were recorded at baseline and after administration of saline or Ang II at 30 min, 1, 2, 6, 12 and 24 h. The evaluation of the baroreflex sensitivity was performed after administration of phenylephrine and sodium nitroprusside. The evaluation of the inflammatory reaction in the aorta was performed by immunohistochemistry, using TGF-β, iNOS as inflammatory markers and CD45 as a marker of macrophages. The evaluation of α-actin was performed in order to demonstrate a possible change in CMLV phenotype. Results: At the end of the treatments, we verified that there was no change in blood pressure or heart rate. In addition, there was a reduction of the tachycardic response in animals receiving Ang II. A biphasic response was observed both for TGF-β expression and for the presence of CD45 positive cells, with an acute increase (between 30 and 60 minutes) and another more chronic increase, between 24 and 48 hours. Positive staining for iNOS increased in longer periods, from 24 to 72 hours. Immunohistochemistry for α-actin showed no alterations, suggesting that the applied dose of angiotensin II does not alter the aortic CMLV phenotype. Conclusions: The results suggest that angiotensin II, even at doses that do not alter blood pressure, is capable of inducing the expression of inflammatory markers and the migration of inflammatory cells into the aorta of normotensive mice. Thus, angiotensin II may be considered to be capable of increasing the propensity to develop a cardiovascular injury, even in normotensive individuals.